Bending and wrinkling of composite fiber preforms and prepregs. A review and new developments in the draping simulations. (15th May 2018) - Boisse, P.; Colmars, J.; Hamila, N.; Naouar, N.; Steer, Q.
Abstract: Bending properties play a significant role in the forming of textile composites reinforcements, particularly in determining the shape of wrinkles. The physics related to the bending of fibrous reinforcements is specific. Bending is due to slippage between the fibers and since the fibers are quasi-inextensible, standard plate and shell theories are irrelevant. To measure bending characteristics, three experimental tests (and their variants) have been developed in the last decades, and efforts are currently devoted to extending and improving these tests. From their results, simulations can be performed by introducing a flexural energy related to the bending moment and the curvature. In particular, wrinkles during forming can be simulated. In the case of 3D modeling of thick reinforcements, the use of generalized continuum mechanics model is necessary because of the bending stiffness of each fiber and the slippage between fibers. In order to simulate textile reinforcements with shells, some shell approaches, different of the standard theories, can correctly calculate the rotations of textile reinforcement normals.